Coronary Angiographic Findings in Diabetic Patients Versus non-Diabetics with Coronary Heart Disease - Kadhim, Akram Rasol; Strak, Sarkis K.; Hazaa, Mazin A. (AL-Kindy College Medical Journal, 2013)
Background :Atherosclerosis is the most frequent underlying cause of ischemic heart disease and a major cause of death all over the world. This study was carried out to analyze and compare the angiographic findings in patients with diabetes mellitus versus non diabetics with coronary heart disease , and to correlate these findings with some risk factors for coronary heart disease. Methods: A total of 100 patients were studied, 50 with diabetes mellitus, and 50 non diabetics. This study was carried out at Al-Sadr teaching hospital in Basrah, Southern Iraq during the period April 2009- September 2009. All patients were known to have coronary heart disease. Risk factors for coronary heart disease were studied and coronary angiography was performed to define coronary lesions for all patients, and were classified into those who had single , two , three or four vessels disease, according to the number of critical coronary vessels involed. Angiography was considered as normal when the test did not identify any obstruction of any major epicardial artery. Results: Diabetic patients had more multi-vessels involvement coronary heart disease than non diabetics. Right coronary artery, left main stem artery, left circumflex artery involvement and left ventricular systolic dysfunction were seen more in diabetics than non diabetic patients. Conclusions: This study showed that diabetic patients had more critical multi-vessels involvement than non diabetic. Diabetic patients had also worse coronary angiographic findings independent on the presence or absence of other risk factors